2022
DOI: 10.1186/s13071-022-05150-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding reveals low prevalence of microsporidian infections in castor bean tick (Ixodes ricinus)

Abstract: Background Microsporidia is a large group of eukaryotic obligate intracellular spore-forming parasites, of which 17 species can cause microsporidiosis in humans. Most human-infecting microsporidians belong to the genera Enterocytozoon and Encephalitozoon. To date, only five microsporidian species, including Encephalitozoon-like, have been found in hard ticks (Ixodidae) using microscopic methods, but no sequence data are available for them. Furthermore, no widespread screening for microsporidian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…ASVs were compared to those in GenBank using the Basic Local Alignment Search Tool for Nucleotides (BLASTN) [ 72 ] (access date: September 2023), optimised for highly similar sequences (MegaBlast algorithm) [ 73 ]. ASVs were compared to GenBank using a 97% identity threshold to determine mosquito species and 100% identity to identify microsporidian species, as described in previous studies [ 5 , 67 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…ASVs were compared to those in GenBank using the Basic Local Alignment Search Tool for Nucleotides (BLASTN) [ 72 ] (access date: September 2023), optimised for highly similar sequences (MegaBlast algorithm) [ 73 ]. ASVs were compared to GenBank using a 97% identity threshold to determine mosquito species and 100% identity to identify microsporidian species, as described in previous studies [ 5 , 67 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen species have been associated with human diseases (Han and Weiss, 2017). However, ticks are probably not vectors of zoonotic microsporidia (Trzebny et al, 2022), but they can occasionally be found infected with these parasites. In general, knowledge on microsporidial infections in ticks is limited and only three species have been detected in I. ricinus by microscopic methods: Nosema slovaca and Unikaryon (Nosema) ixodis in former Czechoslovakia by Weiser and Rehaćek (1975) and Weiser et al (1999) and a Nosema-like species in Moldova by Tokarev Iu and Movilé(2004).…”
Section: Microsporidiamentioning
confidence: 99%
“…Recently, metabarcoding revealed low prevalence of microsporidian parasites in questing I. ricinus and in those collected from dogs in Poland. Encephalitozoon intestinalis , a potentially zoonotic species was detected in ticks that fed on dogs and a potentially new Endoreticulatus species in questing ticks ( Trzebny et al., 2022 ). Nosema slovaca was also detected and isolated from D. reticulatus collected in Hungary.…”
Section: Pathogensmentioning
confidence: 99%